VIBRATION FATIGUE ANALYSIS AND OPTIMAL DESIGN OF ALTERNATOR BRACKET - LU Jian; ZHONG ZiFeng (Jixie qiangdu)
Aiming at of solving the cracking problem of an alternator bracket. Firstly, the engine time domain-acceleration curve were tested, and they were converted to frequency domain acceleration curve. The alternator bracket was frequency response analyzed based on the frequency domain acceleration curve, the analysis results show that the maximum stress value exceeded the yield strength of the material. Secondly, the alternator bracket was vibration fatigue analyzed by adopting power spectrum density function, the analysis results show that the minimum life was lower than target, and it was consistent with the strength analysis weak region and actual failure position. Thirdly, the alternator bracket was optimal designed by adopting large scale generalized reduced gradient algorithm, it can meet fatigue and strength performance requirements after optimization. Lastly, the alternator bracket optimization scheme was certificated by vehicle road test, the test results show that the alternator bracket vibration amplitude is obviously decreased, and the alternator bracket cracking is avoided, so the cracking problem is effectively solved. A scientific references are provided for the high frequency response bracket failure solution by the analysis method and its optimization method.